1994
DOI: 10.1116/1.579001
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy analysis of aluminum and copper cleaning procedures for the Advanced Photon Source

Abstract: The Advanced Photon Source (APS), presently under construction, will produce x rays of unprecedented brightness. The storage ring where the x rays will be produced will be constructed from an extruded 6063 aluminum alloy, while transition pieces (flanges, etc.) will be made from a 2219 aluminum alloy. In addition, cooled photon absorbers will be placed in strategic locations throughout the ring to intercept the majority of the unused high power-density radiation. These will be made of either CDA-101 (OFHC) cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Aluminum alloy can be a source of outgassing because a natural oxide layer with a thickness of 10 nm or more is formed on the surface of the alloy after machining. This porous oxide layer can readily adsorb impurities and gasses that can be released in vacuum42. These results shed new light on some of the factors affecting the reproducibility of OLED lifetime, which is one of the great mysteries of OLEDs.…”
Section: Discussionmentioning
confidence: 91%
“…Aluminum alloy can be a source of outgassing because a natural oxide layer with a thickness of 10 nm or more is formed on the surface of the alloy after machining. This porous oxide layer can readily adsorb impurities and gasses that can be released in vacuum42. These results shed new light on some of the factors affecting the reproducibility of OLED lifetime, which is one of the great mysteries of OLEDs.…”
Section: Discussionmentioning
confidence: 91%
“…Cleaning of aluminum alloy 6xxx series has been previously found to be most effective with mild alkaline detergents such as Almeco 18; surfaces cleaned with such detergents were found to have a thinner oxide, well depleted of Mg, compared to surfaces cleaned with strong alkaline detergents or solvents only [3]. Moffitt and co-workers found that an acid pickle was highly effective in removing Mg [11].…”
Section: Surface Electrostatics Characterizationmentioning
confidence: 96%
“…There are many large vacuum facilities requiring highcleanliness conditions, such as particle accelerators. Literature concerning the cleaning procedures used for vacuum chamber construction materials describes the use of alkaline detergent washing followed by deionized water rinsing for aluminum alloys (see, for example, [2][3][4][5]). However, to our knowledge, the use of a phosphoric acid etch prior to alkaline detergent washing has not been previously described as a standard cleaning protocol for aluminum vacuum chamber parts, nor has the problem of "smut" (loosely attached oxide and surface adsorbed particles) been addressed in this context.…”
Section: Introductionmentioning
confidence: 99%